2020
DOI: 10.1016/j.diabres.2020.108346
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid diabetes and the risk of disease severity or death among 8807 COVID-19 patients in China: A meta-analysis

Abstract: Diabetes mellitus has been reported to be one of the most prevalent comorbidity in patients with Coronavirus Disease 2019 (COVID-19). We aimed to assess the association of comorbid diabetes with COVID-19 severity or mortality in China. Methods: We performed a systematic literature search from six electronic databases on diabetes and COVID-19. The outcome of interest was disease severity or mortality. Heterogeneity among the studies was assessed by the Cochran Q test and the I 2 statistic. A random effects mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 40 publications
6
72
1
7
Order By: Relevance
“…In our study, diabetes was more common in patients with COVID-19 and was associated with an increased risk of death. This finding is in accordance with a meta-analysis that analyzed the association between comorbid diabetes and disease severity or death [35,36]. As shown in our study, diabetes is one of the most prevalent comorbidities in patients with COVID-19, and there is a significant association with a greater severity of the illness or death in primary care; this association is in line with in-hospital mortality for patients with COVID-19, for which up to a 3-fold increased risk has been found [37].…”
Section: Principal Findingssupporting
confidence: 89%
“…In our study, diabetes was more common in patients with COVID-19 and was associated with an increased risk of death. This finding is in accordance with a meta-analysis that analyzed the association between comorbid diabetes and disease severity or death [35,36]. As shown in our study, diabetes is one of the most prevalent comorbidities in patients with COVID-19, and there is a significant association with a greater severity of the illness or death in primary care; this association is in line with in-hospital mortality for patients with COVID-19, for which up to a 3-fold increased risk has been found [37].…”
Section: Principal Findingssupporting
confidence: 89%
“…However, another study with a larger sample size found that AST abnormality, rather than bilirubin, was strongly associated with COVID-19 mortality risk [ 20 ]. A recent meta-analysis concluded that comorbid diabetes was associated with an increased risk of disease severity or death in Chinese COVID-19 patients, while it is still not clear to what extent diabetes independently contributes to the increased risk [ 21 ]. Besides, acute kidney injury is associated with severe infection and fatality in patients with COVID-19 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a common comorbidity in COVID‐19 patients 5 and was suggested to be a risk factor of severe and fatal COVID‐19 cases 12 . A meta‐analysis showed that COVID‐19 patients with diabetes had a higher risk (risk ratio [RR]: 2.96; 95% CI: 2.31−3.79) of severe disease or death, 69 and higher rate of ICU admissions 70 . In a cohort study of COVID‐19 patients from New York City (USA), those with diabetes had an increased risk of hospital admission (OR: 2.24; 95%CI: 1.84−2.73) and critical illness (OR: 1.24; 95%CI: 1.03‐1.50) 50 .…”
Section: Comorbiditiesmentioning
confidence: 99%